Frozen orbit - Chiles, Patrick (Baen Books, 2020)
"When a tiny space probe hurtled past Pluto in 2015, no one could know that its most amazing discovery would remain hidden for years. Only when a long-lost Soyuz is destroyed in the skies above Siberia does the truth begin to emerge. About to embark on NASA's first expedition to the outer planets, the crew of the spacecraft Magellan learns someone else has beaten them by a few decades: a top-secret Soviet project codenamed Arkangel. It was a mission that began before most of them were even born, and the Kremlin believes it drove their most trusted crew mad. During their long race to the Kuiper Belt, astronauts Jack Templeton and Traci Keene unwind a decades-old mystery buried in the pages of a dead cosmonaut's journal. Challenging their own beliefs about the nature of humanity, they will soon confront the question of existence itself"--